Kontribusi Pengawasan Kepala Sekolah terhadap Kinerja Guru SMK Negeri Kota Pariaman - Mimi Trida Yanti; Anisah Anisah (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
This article aims to describe teacher performance, principal control, and the contribution of principal control to teacher performance. The type of research is a correlational quantitative research. The study population amounted to 298 teachers, the sample was taken 84 teachers using Proportional Stratified Random Sampling technique. Data were collected with a Likert scale model questionnaire that had been tested for validity and reliability. The data were analyzed used by the Product Moment Correlation formula. Results of study show that the value of 0.535 is greater than 0.215 at a significant level of 5%. Teacher performance is good with an average achievement level of 89.41% of the ideal score. Principal control is good with an average achievement level of 80.09% of the ideal score. Furthermore, after testing the Coefficient of Determination, the result is 0.286. The results indicate that the hypothesis that there is a significant contribution of principal control to teacher performance can be accepted, which is 28.6%, while 71.4% is influenced by other factors.